Buckwheat Forage as a Ruminant Feed: The Effects of Different Harvesting Stages on the Nutritive Value and Yield of Two Cultivars - Hanoğlu Oral, H (Journal of the Hellenic Veterinary Medical Society, 2024)
This study was performed to investigate the effects of harvesting stages on the chemical constituents, energy values, in vitro true dry matter digestibility (IVTDMD), forage yield, and relative feed values (RFV) of buckwheat (Fagopyrum esculentum Moench), cultivars, Aktaş and Güneş, developed in Turkey. Buckwheat forage was harvested at following three stages: the early dough (ED) stage, the soft-to-hard dough (SHD) stage, and the fresh stover (S) stage. The forage dry matter (DM) yields of the Aktaş and Güneş cultivars were 458.63 and 479.02 kg /da respectively, and no significant difference was found between the cultivars in terms of the forage DM yield, chemical constituents, energy values, IVTDMD and RFV (P>0.05). The forage yield was primarily affected by the harvesting stage. The forage DM yield for the average of the two cultivars increased by about 27% from the ED to the SHD stage, but decreased by about 62% from the ED to the S stage. Significant differences were observed between the S stage and the other two harvest stages in terms of chemical constituents, energy values, IVTDMD and RFV, and the lowest nutritive values were obtained at the S stage (P<0.05). In both buckwheat cultivars, the highest crude protein (CP) and IVTDMD were obtained at the ED stage, but CP yield and digestible dry matter yield were found to be highest at the SHD stage. Therefore, it is strongly recommended that the buckwheat cultivars Aktaş and Güneş should be harvested at the SHD stage. The CP content of the fresh stover was 8.90% since the fresh buckwheat stover, remained in the field after the grain harvest, contained flowers, green seeds and mature seeds besides leaves and stems, which were green during this period. However, the IVTDMD value was found to be as low as 47.92%, indicating a reduction in forage quality.